Grape seed extract protects against amiodarone - induced nephrotoxicity and ultrastructural alterations associated with the inhibition of biomarkers of inflammation and oxidative stress in rats. (2nd January 2021) - Eid, Refaat A.; Zaki, Mohamed Samir Ahmed; Al-Shraim, Mubarak; Eldeen, Muhammad Alaa; Haidara, Mohamed A.
ABSTRACT: Amiodarone (AMD) is one of the highly effective antiarrhythmic agents used for treating refractory arrhythmias. It is well known to have long-term administration side effects such as nephrotoxicity. The possible ameliorative effects of antioxidant grape seed extract; on the extent of tissue damage in AMD-induced nephrotoxicity has not been investigated before. Twenty-four albino rats were used in this study and divided into four groups (n = 6). The 1 st group served as an untreated control group, under the same laboratory conditions, the 2 nd group received (100 mg/kg/day) of grape seed extract (GSE), the 3rd group, AMD-treated group, received AMD (40 mg/kg/day) and the 4th group received both AMD and GSE in the same doses as the previous groups. AMD-treated group showed abnormal glomerular capillaries with wrinkling basement membranes damaged mesangial cells and distorted proximal tubules with plenty of lysosomes. Ultrastructural alterations were also observed in this group. This was also associated with a significant increase in biomarkers of kidney injury (creatinine), oxidative stress ((Decreased SOD and increased MDA) and biomarkers of inflammation IL-6) in comparison to the control group. Supplementation of GSE to AMD group for eight weeks counteracted these effects. It caused an improvement in histological and t ultrastructure changes of the renal tissues associated with decreased creatinine and biomarkers of oxidative stress and inflammation in comparison to AMD-treated group. We conclude that GSE protects against AMD-induced kidney injuries in rats, which is associated with the inhibition of biomarkers of inflammation and oxidative stress.